2022
DOI: 10.1186/s12958-022-00919-0
|View full text |Cite
|
Sign up to set email alerts
|

Activation of AKT/mammalian target of rapamycin signaling in the peripheral blood of women with premature ovarian insufficiency and its correlation with FMR1 expression

Abstract: Background The protein kinase B (AKT)/mammalian target of rapamycin (mTOR) signaling pathway regulates early follicular activation and follicular pool maintenance in female germline cells. Fragile X mental retardation 1 (FMR1) regulates folliculogenesis and it is variably expressed in patients with Premature Ovary Insufficiency. FMR1 expression is supposed to be linked to AKT/mTOR signaling in an ovarian response dependent manner as demonstrated in recent invitro and invivo studies in the femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…In the past decades, many studies have revealed the nutrient composition of the diet is important for homeostasis. Specifically, it has been reported the amino acid sensing protein mTOR is an important factor in the development of POI (Rehnitz et al , 2022 ; Xu et al , 2022 ). These results suggested that amino acid metabolism might have significant impacts on POI.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decades, many studies have revealed the nutrient composition of the diet is important for homeostasis. Specifically, it has been reported the amino acid sensing protein mTOR is an important factor in the development of POI (Rehnitz et al , 2022 ; Xu et al , 2022 ). These results suggested that amino acid metabolism might have significant impacts on POI.…”
Section: Discussionmentioning
confidence: 99%
“…Although it did not reach significance, a trend for an increase in the phosphorylation of ERK1/2 in the medial prefrontal cortex was noted. The phosphorylation of mTOR positively regulates the phosphorylation of the FMRP, the FMRP kinase S6K, and negatively regulates the activity of the FMRP phosphatase PP2Ac [ 33 , 34 , 35 ]. Thus, a transient decrease in the phosphorylation of mTOR may be a novel, non-canonical mechanism by which to induce translational events that induce long-lasting synaptic changes.…”
Section: Discussionmentioning
confidence: 99%
“…The AKT/mTOR signaling pathway controls ovarian folliculogenesis by maintaining the PMF pool, including PMF activation, GC proliferation, and oocyte-GC intercellular communication (175). Studies have shown significant activation of the AKT/ mTOR/S6K signaling pathway in humans with POI (176). Therefore, regulating the AKT/mTOR/S6K signaling pathways, such as AKT activators and mTOR activators, can induce further follicular maturation and development in women with POI (176).…”
Section: Mtor/s6 Kinase Pathway Interventionsmentioning
confidence: 99%
“…Studies have shown significant activation of the AKT/ mTOR/S6K signaling pathway in humans with POI (176). Therefore, regulating the AKT/mTOR/S6K signaling pathways, such as AKT activators and mTOR activators, can induce further follicular maturation and development in women with POI (176).…”
Section: Mtor/s6 Kinase Pathway Interventionsmentioning
confidence: 99%